Radiation exposure to the lens of the eye for Japanese nuclear power plant workers. (1st September 2022) - Yokoyama, Sumi; Tatsuzaki, Hideo; Tanimura, Yoshihiko; Yoshitomi, Hiroshi; Hirao, Shigekazu; Aoki, Katsunori; Tachiki, Shuichi; Ezaki, Iwao; Hoshi, Katsuya; Tsujimura, Norio
Abstract: In Japan, the radiation-dose limit for the lens of the eye was revised in April 2021. Consequently, for workers, the numerical values of the equivalent dose to the lens of the eye are equal to those of the effective dose. Radiation workers, radiation safety officers and licensees must comply with regulations related to radiation protection and optimize protection. The new guidelines on dose monitoring of the lens of the eye developed by the Japan Health Physics Society recommend for the dose to be estimated near the eye for accurate estimation, when the dose to the lens approaches or exceeds the management criteria. However, there is limited information regarding the non-uniform exposure of nuclear power plant workers. In this study, the dose equivalents of high-dose-rate workplaces and the personal doses of 88 workers were estimated at four Japanese commercial nuclear power plant sites (RWR: 3 units and BWR: 3 units) and the dose to the lens of the eye and the exposure situations of the workers were analyzed.